MAKTABGACHA YOSHDAGI BOLALARNING TARBIYASIDA MILLIY URF-ODATLAR, QADRIYATLAR VA AN’ANALARNI ZAMONAVIY TEXNOLOGIYALAR ORQALI SINGDIRISH - Soliyev Ilhom Sobirovich, To‘ychiyeva Shoxidaxon Qaxramon qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This scientific article analyzes the importance of instilling national customs, values and traditions through modern technologies in the education of preschool children. Today, the rapid development of technologies creates new opportunities for the introduction of innovations in education and their integration while preserving national values in the process of raising children. Modern technologies play a major role in shaping children's cultural identity and making education more effective with the help of various applications and technologies. Based on research and experience, this article talks about how modern technologies can be used as a useful tool in education and upbringing of children.